Leaving no one behind in armed conflict-affected settings of Africa: is universal health coverage a possibility or mirage? - Olushayo Oluseun Olu; Amos Petu; Abdulmumini Usman (BMC, 2024)
Abstract The world is off track six years to the 2030 deadline for attaining the sustainable development goals and universal health coverage. This is particularly evident in Africa's armed conflict-affected and humanitarian settings, where pervasively weak health systems, extreme poverty and inequitable access to the social dimensions and other determinants of health continue to pose significant challenges to universal health coverage. In this article, we review the key issues and main barriers to universal health coverage in such settings. While our review shows that the current health service delivery and financing models in Africa's armed conflict-affected settings provide some opportunities to leapfrog progress, others are threats which could hinder the attainment of universal health coverage. We propose four key approaches focused on addressing the barriers to the three pillars of universal health coverage, strengthening public disaster risk management, bridging the humanitarian-development divide, and using health as an enabler of peace and sustainable development as panacea to addressing the universal health coverage challenge in these settings. The principles of health system strengthening, primary health care, equity, the right to health, and gender mainstreaming should underscore the implementation of these approaches. Moving forward, we call for more advocacy, dialogue, and research to better define and adapt these approaches into a realistic package of interventions for attaining universal health coverage in Africa's armed conflict-affected settings.